2017
DOI: 10.1111/bdi.12529
|View full text |Cite
|
Sign up to set email alerts
|

Total sleep time and kynurenine metabolism associated with mood symptom severity in bipolar disorder

Abstract: Inflammation, sleep, and mood are closely intertwined. Future research into the effect of inflammation on sleep in BD may lead to clinical markers of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
3
30
1
2
Order By: Relevance
“…In this sense, our data are in line with the literature, where meta-analyses have shown significant alterations in interleukins in BD patients compared to HC, including IL-4, IL-6 and IL-10 (Modabbernia et al, 2013;Munkholm et al, 2013). Moreover, these alterations in patients with BD have been linked to severity of symptoms (Mukherjee et al, 2018), mood episodes (Kapczinski et al, 2010), staging (Kauer-Sant'Anna et al, 2009) and medication use (Lim et al, 2016). Regarding MDD, a meta-analysis has shown that IL-1, IL-6 and TNF-α levels in peripheral blood are increased in patients compared to HC (Dowlati et al, 2010), while another meta-analysis has described alterations in IL-10 levels while findings in IL-4 and IL17-A levels are still heterogeneous (Köhler et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, our data are in line with the literature, where meta-analyses have shown significant alterations in interleukins in BD patients compared to HC, including IL-4, IL-6 and IL-10 (Modabbernia et al, 2013;Munkholm et al, 2013). Moreover, these alterations in patients with BD have been linked to severity of symptoms (Mukherjee et al, 2018), mood episodes (Kapczinski et al, 2010), staging (Kauer-Sant'Anna et al, 2009) and medication use (Lim et al, 2016). Regarding MDD, a meta-analysis has shown that IL-1, IL-6 and TNF-α levels in peripheral blood are increased in patients compared to HC (Dowlati et al, 2010), while another meta-analysis has described alterations in IL-10 levels while findings in IL-4 and IL17-A levels are still heterogeneous (Köhler et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Replicated evidence has demonstrated sleep dysfunction to be associated with increased levels of pro-inflammatory cytokines with a bidirectional causal association identified [ 106 , 107 ]. As such, interest has grown in immune dysfunction as a potential nexus sub-serving the bidirectional interaction between sleep dysfunction and BD [ 108 , 109 ].…”
Section: Pathophysiology Of the Inflammatory-mood Pathwaymentioning
confidence: 99%
“…Aberrant sleep is associated with increased levels of proinflammatory cytokines with a bidirectional causal association identified (154, 155). As such, interest has grown in immune dysfunction as a potential link that underwent two-way interaction between sleep dysfunction and BD (156, 157). Both postmortem and in vivo studies showed that microglial activation is involved in the neurobiology of BD (158, 159).…”
Section: Sleep Astroglia and Bipolar Disordermentioning
confidence: 99%